A Nationwide Analysis of Outcomes of Weekend Admissions for Intracerebral Hemorrhage Shows Disparities Based on Hospital Teaching Status. (April 2016) - Patel, Achint A.; Mahajan, Abhimanyu; Benjo, Alexandre; Pathak, Ambarish; Kar, Jitesh; Jani, Vishal B.; Annapureddy, Narender; Agarwal, Shiv Kumar; Sabharwal, Manpreet S.; Simoes, Priya K.; Konstantinidis, Ioannis; Yacoub, Rabi; et al.
Background and Purpose: With the "weekend effect" being well described, the Brain Attack Coalition released a set of "best practice" guidelines in 2005, with the goal to uniformly provide standard of care to patients with stroke. We attempted to define a "weekend effect" in outcomes among patients with intracranial hemorrhage (ICH) over the last decade, utilizing the Nationwide Inpatient Sample (NIS) data. We also attempted to analyze the trend of such an effect. Materials and Methods: We determined the association of ICH weekend admissions with hospital outcomes including mortality, adverse discharge, length of stay, and cost compared to weekday admissions using multivariable logistic regression. We extracted our study cohort from the NIS, the largest all-payer data set in the United States. Results: Of 485 329 ICH admissions from 2002 to 2011, 27.5% were weekend admissions. Overall, weekend admissions were associated with 11% higher odds of in-hospital mortality. When analyzed in 3-year groups, excess mortality of weekend admissions showed temporal decline. There was higher mortality with weekend admissions in nonteaching hospitals persisted (odds ratios 1.16, 1.13, and 1.09, respectively, for 3-year subgroups). Patients admitted during weekends were also 9% more likely to have an adverse discharge (odds ratio 1.09; 95% confidence interval: 1.07-1.11; P < .001) with no variation by hospital status. There was no effect of a weekend admission on either length of stay or cost of care. Conclusion: Nontraumatic ICH admissions on weekends have higher in-hospital mortality and adverse discharge. This demonstrates need for in-depth review for elucidating this discrepancy and stricter adherence to standard-of-care guidelines to ensure uniform care.